A Survival Nomogram Containing Lymph Node Ratio for Hypopharyngeal Carcinoma Patients After Neck Dissection. (19th January 2023) - Li, Feiran; Huang, Qiang; Hsueh, Chiyao; Huang, Huiying; Zhu, Yi; Gong, Hongli; Tao, Lei; Zhou, Liang; Zhang, Ming
Abstract: Objective: The purpose of our study is to establish a survival nomogram based on lymph node ratio (LNR) in hypopharyngeal carcinoma. Study Design: Retrospective cohort study. Setting: Hypopharyngeal squamous cell carcinoma (HPSCC) is prone to regional metastasis. Emerging evidence has shown that LNR is a promising prognostic factor in HPSCC. Methods: From January 2004 to January 2018, 411 HPSCC patients who underwent neck dissection at our institution were retrospectively studied. The enrolled patients were divided into training and validation cohorts at a ratio of 7:3. A survival nomogram was finally built based on factors screened from multivariate analysis using the bidirectional stepwise method. Results: LNR was superior to other nodal classifications for survival prediction and was used to establish the R classification. A nomogram was developed using R classification ( p  < .001), pT classification ( p  < .001), tumor invasive depth ( p  < .001), and internal jugular vein adhesion ( p  = .001). The C ‐indexes were 0.712 and 0.703 in the training and validation dataset. The 36‐ and 60‐month AUCs were 0.767 and 0.766 in the training dataset and 0.713 and 0.757 in the validation dataset, respectively. The calibration curves showed relatively good agreement between the predicted and actual probability. Conclusion: Based on the LNR, we developed a survival nomogram for HPSCC after neck dissection, which will be a practical tool to discriminate patients with different survival risks.